Verbalisation of encouragement in contemporary French dialogic discourse - Nataliia V. Poliakova; Victoria V. Sibul (Peoples' Friendship University of Russia (RUDN University), 2021)
The article conducted in the framework of the communicative-pragmatic paradigm of knowledge focuses on the analysis of linguistic means of encouraging the interlocutor on the recipient's end in the course of polite, socially acceptable communication that is also called conventional. The main objective of the article is to identify stereotypical ways of verbalising the tactics of speech behaviour of the recipient, which consists in encouraging the interlocutor in French dialogic discourse. The consideration of the nature and peculiar features of the speech act as a unit of normative socio-speech behaviour is of great theoretical interest as it helps examine the mechanisms of speech and identify specific trends, and practical significance, for example, for the adequate identification and description of discursive strategies to the full extent. The material of this study includes dialogic unities from the fictional works of contemporary French authors, in which the speech of the characters closely resembles spontaneous spoken interaction. The study concludes that the verbal behaviour of the recipient should take into account the duality of their position as they act not only as an object of speech persuasion but also as a subject of speech interaction. The analysis of the speech act of agreement, as one of the most important for dialogic communication, made it possible to single out a variety of communicative units involved in its implementation, as well as to reveal the diversity of the modal characteristics transmitted by them.